(untitled) (Community Based Medical Journal, 2022)
The COVID-19 pandemic left impact on domestic violence, sexual assault and increases the pandemic related rape cases in Bangladesh. The present study aimed to give an overview COVID-19 related rape cases so that awareness can be created among public in the outbreak. Three English and Bangla online news portals were selected purposively to include in the study and news of „Rape Case‟ were searched. Search was conducted by the word “rape news”. After removal of the repetitions news, we select ten news that reported detailed rape cases during the country wide lockdown. From ten rape cases, age of victim ranges from 8-23, the victim of eight rape cases were below 18 years (In some cases the age of the victim were not mentioned). In addition, there were five incidents of gang rape, one rape attempts and among ten cases seven of the rape were general types. Additionally, the majority of rape cases occurred at rural areas. Women of all ages are at risk of rape during the pandemic and particular attention should be given to rural areas, as most cases of rape are registered there. Public awareness about rape would be effective to report in due time with preserving the evidence of crime. CBMJ 2021 January: vol. 10 no. 01 P: 43-49